HUBUNGAN SELF RESILIENCE DENGAN PERILAKU AGRESIF PENYALAHGUNA NARKOBA DI TEMPAT PUSAT REHABILITASI BNN LIDO - Sheila Virginia Agisna; Titik Haryati (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2021)
This research is motivated by the phenomenon of high cases of drug abusers, especially in young people or productive age in early adulthood until now. Early adulthood is faced with a period of forming personal independence where the roles and responsibilities they face are getting bigger, so it is possible to fall into drug abuse. Rehabilitation institutions, including BNN, prioritize the recovery of drug abusers. The challenges and obstacles experienced by addicts towards recovery are very heavy, the adjustments that drug abusers undergo during rehabilitation will lead to bad attitudes to commit many violations including aggressive behavior. In order for individuals to be able to remain calm under pressure or difficult conditions and be able to control their thoughts and behavior, including aggressive behavior, self resilience is needed. This study aims to see and describe the relationship between self resilience and aggressive behavior of drug abusers. The population in this study were 168 early adult drug abusers at BNN Lido Bogor with a total sample of 42 people using the nonprobability sampling method with purposive sampling technique. The data collection technique uses an aggressiveness scale of 29 valid items and a resilience scale of 48 valid items with the product moment correlation validity formula. The data analysis technique used is the Pearson product moment correlation from Kearl Pearson. The results showed that there was a negative correlation between self resilience and aggressive behavior of drug abusers. The relationship is shown by the results of calculations using the Pearson product moment correlation, with a significance level of = 0.05 where the correlation value is -0.692 and the significance value of the self resilience variable and aggressive behavior is 0.000. Value of Sig. 0.000 < 0.05 then H1 is accepted. From these results, it can be understood that the higher the level of self-resilience, the lower the aggressive behavior that appears and vice versa.